THE RELATIONSHIP BETWEEN MANAGERIAL OVERCONFIDENCE, LEVERAGE, AND MANAGERIAL OWNERSHIP AND EARNINGS MANAGEMENT - Ni Putu Sisca Damayanti; Gerianta Wirawan Yasa (Adisam Publisher, 2026)
Earnings information in financial statements serves as a primary reference for evaluating corporate performance and strategic decision-making. Amid increasing pressure and uncertainty in a dynamic business environment, earnings management practices are often employed by management as a response to external expectations and internal constraints, reflecting agency problems arising from misaligned interests between capital providers and managers as decision-makers. This study aims to obtain empirical evidence on the relationship between managerial overconfidence, leverage, and managerial ownership and earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling, resulting in 128 firms with a total of 640 firm-year observations. Data were analyzed using multiple linear regression with SPSS software. The results indicate that managerial overconfidence is negatively associated with earnings management, while leverage is positively associated with earnings management. Meanwhile, managerial ownership shows no significant relationship with earnings management. These findings emphasize that financial pressure, as reflected by high leverage, plays a more dominant role in driving earnings management practices than managerial overconfidence or managerial ownership. Accordingly, firms with higher leverage levels tend to have a stronger inclination to engage in earnings management as a response to external financial obligations.